Etnobiologi Dan Interdependensi Masyarakat Terhadap Kawasan Konservasi (Studi Masyarakat Sekitar Taman Wista Alam Klamono Papua Barat Daya) - Maruapey, Azis; Nanlohy, Lona Helti; Saeni, Fajrianto (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
As a conservation area, the Klamono Nature Tourism Park is also expected not only for tourism purposes, but also as a life support area for the surrounding community who are dependent on natural resources, both wood and non-timber forest products. The method used in this research is a descriptive method with survey techniques and semi-structural interviews. The results of the research show communally that the community in utilizing the Klamono Nature Tourism Park conservation area is farming, hunting and gathering which is of ethnobiological significance and interdependence (dependence) on the availability of forest resources in the park area. Ethnobiology and community interdependence are interpreted by the perception that forests are a source of food, forests are a source of medicines, forests are a source of building materials, forests are a source of firewood and forests are a source of cash income.